Effectiveness and equity of mHealth apps for preeclampsia management in LMICs: A rapid review protocol. - Abdirahman Moallim Ibrahim; Shayesteh Jahanfar (PLoS ONE)
Introduction Preeclampsia remains a formidable public health challenge, particularly in low- and middle-income countries (LMICs), where it significantly contributes to the high rates of maternal and neonatal morbidity and mortality. The advent of mobile health (mHealth) applications presents a promising avenue for enhancing the management of preeclampsia. This review protocol is designed to systematically assess the effectiveness and equity of mHealth apps in managing preeclampsia within LMICs, with a focus on clinical outcomes and the broader implications for accessibility, affordability, and cultural relevance. Materials and methods To achieve the objectives of this review, a rapid review methodology will be employed, encompassing a structured search strategy to identify pertinent studies from databases such as PubMed, Cochrane Library, and Google Scholar, as well as grey literature. The inclusion criteria are set to encompass randomized controlled trials (RCTs), controlled clinical trials (CCTs), observational studies, and qualitative studies that offer insights into the effectiveness and user experience of mHealth apps for preeclampsia management. Participants in these studies will include pregnant women at risk for or diagnosed with preeclampsia, healthcare providers, and app developers. The quality of the included studies will be critically appraised using standardized tools, and data extraction will focus on study characteristics, interventions, outcomes, and equity considerations. Discussion The implications of this review are far-reaching, offering the potential to inform stakeholders including policymakers, healthcare providers, and app developers about the deployment and development of mHealth solutions for preeclampsia management in LMICs. Ultimately, the anticipated findings of this review are expected to contribute significantly to the understanding of mHealth apps' role in improving preeclampsia management and addressing healthcare disparities, thereby guiding future strategies to enhance maternal and neonatal health outcomes in LMICs.